Teaching scientific method to primary school pupils by using the example of adaptation of secondarily aquatic animals to the marine environment - Antczak, Mateusz (Geologos, 2021)
Science classes in public schools are usually strictly linked to several subjects and taught by reference to the reading-listening model. Non-formal educational institutions and events such as ‘children universities’ and science fairs (and to some degree also some private schools) implement elements of interdisciplinary teaching of science and learning through experiments and the use of scientific methods. Workshops conducted within non-formal educational structures prove that only is this method engaging and understandable to primary school pupils, it also is possibly much more effective than the traditional learning style for coding information and explaining common misconceptions in teaching evolution, palaeontology and biodiversity. The example of a scenario for science classes presented here (the so-called ‘aquatic problem’, i.e., adaptations of primarily terrestrial animals – amniotes – to the aquatic environment) uses simple props, such as everyday items, to address the problems that teachers in public school face. Thus, it can be implemented independently of school budgets and availability of school equipment.